2012
DOI: 10.1080/14763141.2011.650187
|View full text |Cite
|
Sign up to set email alerts
|

Movement variability in the golf swing

Abstract: Traditionally, golf biomechanics has focused upon achieving consistency in swing kinematics and kinetics, whilst variability was considered to be noise and dysfunctional. There has been a growing argument that variability is an intrinsic aspect of skilled motor performance and plays a functional role. Two types of variability are described: 'strategic shot selection' and 'movement variability'. In 'strategic shot selection', the outcome remains consistent, but the swing kinematics/kinetics (resulting in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 43 publications
(72 reference statements)
1
59
0
2
Order By: Relevance
“…The players were instructed to attempt to hit the same type of shot each time and were reminded of this requirement throughout the testing. This was to avoid multiple shot strategies being used and adding confounding variables to the data (see Langdown et al (2012) for "strategic shot selection" vs "movement variability"). All shots, regardless of outcome, were recorded for analysis.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The players were instructed to attempt to hit the same type of shot each time and were reminded of this requirement throughout the testing. This was to avoid multiple shot strategies being used and adding confounding variables to the data (see Langdown et al (2012) for "strategic shot selection" vs "movement variability"). All shots, regardless of outcome, were recorded for analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…More specifically they suggest that it has yet to be clearly identified which coordinative pattern should be allowed to vary and which should be invariant in the golf swing. Although recent reviews have attempted to clarify the structure of movement variability (Glazier, 2011;Knight, 2004;Langdown, Bridge, & Li, 2012), there still remains a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…the hips, torso, arms and club head. 41 In order to achieve optimal energy transfer and club head speed through this proximal to distal sequencing during the downswing, Cheetham et al 11 identified several attributes to be present in the golfer's kinematic sequence, namely:…”
Section: Figurementioning
confidence: 99%
“…The goal of the game is to get the ball into a hole using the fewest number of strokes [2], which is possible with a high driving distance. The distance is determined by the initial ball speed at club impact, and the speed of the ball is a determined by the club head speed immediately before impact [1].…”
Section: Introductionmentioning
confidence: 99%